Antiviral compounds in marine algae, soft coral and sponge: a systematic review - Setyaningrum, Tri Wahyu; Candri, Dining Aidil; Ghazali, Mursal; Prasedya, Eka Sunarwidhi; Faturrahman, Faturrahman; Rozikin, Rozikin (Jurnal Biologi Udayana; Vol 28 No 2 (2024): JURNAL BIOLOGI UDAYANA, 2025)
Diseases caused by viruses are always evolving due to the mutating nature of viruses and are still a threat to the health world today. One of the strategies utilized by scientists to address this challenge is the identification of bioactive compounds with antiviral properties. This article presents an overview of various marine organisms that contain antiviral compounds, including microalgae, macroalgae, soft coral, and marine sponge. This review article employs a systematic review methodology, utilizing Proquest, MDPI, and Science Direct data search bases from 2013 to 2024. The search terms employed were "Antiviral Compounds," "Marine antiviral," "Algae antiviral," "Soft Coral antiviral," and "Sponge antiviral." A total of 440 articles were identified through the use of the specified keywords. Following the screening process, 31 articles were deemed relevant for inclusion in the review. From the 31 selected articles, six articles discussed on microalgae, 11 articles for macroalgae, eight for soft corals, and six for sponges contain antiviral compounds with diverse anti-viral mechanisms. The antiviral compounds identified in the organisms discussed in this article are fatty acid group, lutein, carrageenan, fucoidan, polyphenol group, terpenoid group, sesterpenes, asteltoxin, and others.